Transcatheter Aortic Valve Replacement for Isolated Aortic Regurgitation Using a New Self-Expanding TAVR System - Adam, Matti; Tamm, Alexander; Wienemann, Hendrik; Unbehaun, Axel; Klein, Christoph; Arnold, Martin; Marwan, Mohamed; Theiss, Hans; Braun, Daniel; Bleiziffer, Sabine; Geyer, Martin; Goncharov, Arseniy; et al. (Jacc-Cardiovascular Interventions, 2023)
Background: Patients with severe aortic regurgitation (AR) are often not considered for surgery because of increased surgical risk. Because of unique anatomical characteristics among patients with AR, interventional treatment options are limited, and implantation results are inconsistent compared with those among patients with aortic stenosis. Objectives: The authors describe the initial commercial experience of the first Conformité Européenne–marked transfemoral transcatheter aortic valve replacement system (JenaValve Trilogy [JV]) for the treatment of patients with AR. Methods: This multicenter registry included 58 consecutive patients from 6 centers across Germany. Transcatheter aortic valve replacement was performed with the JV system for isolated severe and symptomatic AR. Patient characteristics, primary implantation outcomes, and valve performance up to 30 days were analyzed using Valve Academic Research Consortium 3 definitions. Results: The mean patient age was 76.5 ± 9 years, with a mean Society of Thoracic Surgeons score of 4.2% ± 4.3%. Device success was achieved in 98% of patients. The mean gradient was 4.3 ± 1.6 mm Hg, and no moderate or severe paravalvular regurgitation occurred. No conversion to open heart surgery or valve embolization was reported. There were no major vascular complications or bleeding events. The rate of new permanent pacemaker implantation was 19.6%. At 30 days, 92% of the patients were in NYHA functional class I or II, and the 30-day mortality rate was 1.7%. Conclusions: Treatment of patients with severe symptomatic AR using the transfemoral JV system is safe and effective. Given its favorable hemodynamic performance and low complication rates, this system may offer a new treatment option for patients with AR not suitable for surgery.
CRIS-Team Scopus Importer:2023-09-01
Keywords: aortic regurgitation; JenaValve; paravalvular regurgitation; TAVR